Answer:
well now he has one of the things that he wanted and he has some money in the bank to build up interest or to have for an emergency. it was also good because it was the cheaper of the two items.
have a good day!
(6x^2+5x+1)/(3x^2+4x+1)
= (3x+1)(2x+1)/(3x+1)(x+1)
= (2x+1)/(x+1)
Answer:
-7x + 5
Step-by-step explanation:
2(4x + 1) - 3(5x - 1)
8x + 2 - 3(5x-1)
8x + 2 - 15x + 3
8x + 5 - 15x
-7x + 5
Hope it helped !
Adriel
Ok so 24 of them and that would be ur answer
Answer:
![1\frac{1}{15}](https://tex.z-dn.net/?f=1%5Cfrac%7B1%7D%7B15%7D)
Step-by-step explanation:
Let's use a start by using common denominators.
and ![8\frac{1}{3} = 8 \frac{5}{15}](https://tex.z-dn.net/?f=8%5Cfrac%7B1%7D%7B3%7D%20%3D%208%20%5Cfrac%7B5%7D%7B15%7D)
Now, replace the original equation with the common denominators. ![9\frac{6}{15} - 8\frac{5}{15}](https://tex.z-dn.net/?f=9%5Cfrac%7B6%7D%7B15%7D%20-%208%5Cfrac%7B5%7D%7B15%7D)
Solve! ![9\frac{6}{15} - 8\frac{5}{15} = 1\frac{1}{15}](https://tex.z-dn.net/?f=9%5Cfrac%7B6%7D%7B15%7D%20-%208%5Cfrac%7B5%7D%7B15%7D%20%3D%201%5Cfrac%7B1%7D%7B15%7D)